POLA PEMBERDAYAAN PEGAWAI NEGERI SIPIL DALAM PELAKSANAAN TUGAS ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN LAMPUNG TENGAH - Sigit Setioko (Universitas Muhammadiyah Metro Lampung, 2017)
Charges against qualified employees getting stronger so that the implementation of empowerment in developing HR competencies of civil servants in the Secretariat of the Regional Representatives Council (DPRD)Central Lampungregency had not negotiable. But employees do not seem to understand and carry out their duties and functions, some are employees who understand their duties and functions, but does not perform the job optimally, even some employees consider coming late to the office are common, and they often employees are not present without explanation. The research problem is formulated as follows: